Protected area tourism and management as a social-ecological complex adaptive system - Morse, Wayde C. (Frontiers in Sustainable Tourism, 2023)
This paper is a minireview of systems and resilience approaches to tourism analysis and to protected area management and how the Social Ecological Complex Adaptive Systems (SECAS) framework can help link them together. SECAS is a unique framework that integrates social (Structuration) and ecological (Hierarchical patch dynamics) theories and examines inputs, outputs, and feedback across a variety of hierarchically nested social and ecological systems. After an introduction to the need for continued theoretical development, this paper continues with a review of the origins and previous applications of the SECAS framework. I subsequently highlight how complex adaptive systems and resilience have been presented in the literature as a way to separately study 1) protected area management, 2) protected area tourism/ecotourism and, 3) land use change in adjacent forest and agricultural landscapes. The purpose of this paper is to build on the frameworks described in this literature and link them through the Social Ecological Complex Adaptive Systems (SECAS) framework. I populate the SECAS framework with components identified in literature on protected area management, ecotourism, and land use change to present an example of a full systems perspective. Each component also represents a hierarchically nested system, for example governance systems, health systems, transportation systems, etc. I conclude with a three-step (5 part) multi-scale and temporal method for SECAS research derived from hierarchy and structuration theories.